Analysis of Interest Rate Impact on the Profitability Level of the Banking System in Albania during the Period 2005 -2014 - Ndoka, Sokol; Bozdo, Anilda (European Journal of Economics and Business Studies, 2015)
This study is an analysis of the movement and impact of interest rates on the profitability level of the banking system in Albania. This analysis covers a 10-year timeframe (is organized in three time segments - before, during and after the financial crisis), taking into consideration the critical point of the years 2008-2009 considered as the “peak” of the global financial crisis. Such separation is made in order to see the possible changes of each period of time and to identify the impact differences of this factor in each period of study. This study is based on the hypothesis that the decrease of the interest rate has positively affected the income increase from interest as a result of the impact of two factors, negative levels of Gaps and an increased level of spread toward the average assets. As a matter of fact, it has neutralized on a certain level the other risks such as that of the loan which has dominated over the other risks. This paper is based on an empirical study with secondary quantitative and qualitative data. This study provides a considerable contribution in the framework of identification of factors affecting the profitability of the banking system in Albania, namely in the context of interest rate; In addition, this study aims at highlighting the importance of open Gaps minimization for the efficient profitability increase of the financial system.
Keywords: Albanian banking system, profitability, interest rate risk, Gaps, spreads, movement, global financial crisis.